Iron overload-induced calcium signals modulate mitochondrial fragmentation in HT-22 hippocampal neuron cells. (15th July 2016) - Lee, Dong Gil; Park, Junghyung; Lee, Hyun-Shik; Lee, Sang-Rae; Lee, Dong-Seok
Graphical abstract: Highlights: FAC-induced iron overload causes Drp1-dependent mitochondrial fragmentation and neuronal cell death. Iron overload causes the elevation of intracellular calcium. Iron-induced calcium activates calcineurin via both calmodulin and calpain pathways. Inhibition of Ca 2+ signals related to calcineurin prevented iron overload-induced mitochondrial fragmentation and neuronal cell death. Abstract: Iron is necessary for neuronal functions; however, excessive iron accumulation caused by impairment of iron balance could damage neurons. Neuronal iron accumulation has been observed in several neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease. Nevertheless, the precise mechanisms underlying iron toxicity in neuron cells are not fully understood. In this study, we investigated the mechanism underlying iron overload-induced mitochondrial fragmentation in HT-22 hippocampal neuron cells that were incubated with ferric ammonium citrate (FAC). Mitochondrial fragmentation via dephosphorylation of Drp1 (Ser637) and increased apoptotic neuronal death were observed in FAC-stimulated HT-22 cells. Furthermore, the levels of intracellular calcium (Ca 2+ ) were increased by iron overload. Notably, chelation of intracellular Ca 2+ rescued mitochondrial fragmentation and neuronal cell death. In addition, iron overload activated calcineurin through the Ca 2+ /calmodulin and Ca 2+ /calpain pathways. Pretreatment with the calmodulin inhibitor W13 and the calpain inhibitor ALLN attenuated iron overload-induced mitochondrial fragmentation and neuronal cell death. Therefore, these findings suggest that Ca 2+ -mediated calcineurin signals are a key player in iron-induced neurotoxicity by regulating mitochondrial dynamics. We believe that our results may contribute to the development of novel therapies for iron toxicity related neurodegenerative disorders.